Analysis of Symbols and Meanings of the Anthology of Autumn Tears of Poetry by Fakhrunnas Ma Jabbar - Yuliarza Putri; Sudirman Shomary (UIR Press, 2022)
Words in poetry usually contain symbols and figurative meanings. Given the importance of symbols and figurative meanings in understanding the message in poetry, the authors are interested in conducting a research entitled